Diseño del sistema de gestión en seguridad y salud ocupacional para el cuerpo de bomberos del cantón Salcedo - Silva Acosta, Marco Rodrigo (2015)
This project's main objective is the implementation of a Safety Management System and Occupational Health for the Fire Department of the Canton Salcedo, based on the current organization for compliance with laws, regulations, agreements and commitments at national and international level about the topic. This project proposes the design of a Management System for Occupational Safety and Health Institution, aimed at improving service capacity, working conditions of firefighters and staff by providing an instrument that allows a better development in the activities support, service and support in fighting fires, mitigation of losses, all for the benefit of the community of Canton Salcedo and his environment.